2019
DOI: 10.1080/00051144.2019.1576965
|View full text |Cite
|
Sign up to set email alerts
|

Improved QoS and avoidance of black hole attacks in MANET using trust detection framework

Abstract: In recent times, secured routing is a major research in MANETs. The behaviour of malicious nodes in this network increases the risk of threats and induces abnormal operations in MANETs. This affects the security of data transmitted between the nodes in the network. Hence, an effective technique is needed to prevent the abnormal nodes after the process of detection. In this paper, we propose an improved Trust Detection Algorithm to increase the probability of detection and prevention of Black Hole nodes in MANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The other Cuckoo search and M-tree-based approach were proposed by Babu and Ussenaiah (14) to enhance the Adhoc network's performance. The other heuristic and metaheuristic approaches based on an optimization algorithm were developed by several researchers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) that optimize the network's performance and provide a secure communication environment.…”
Section: Related Workmentioning
confidence: 99%
“…The other Cuckoo search and M-tree-based approach were proposed by Babu and Ussenaiah (14) to enhance the Adhoc network's performance. The other heuristic and metaheuristic approaches based on an optimization algorithm were developed by several researchers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) that optimize the network's performance and provide a secure communication environment.…”
Section: Related Workmentioning
confidence: 99%
“…The resulting method revealed that it enriches the efficiency of factors namely packet delivery ratio, end-end-delay and hop to sink delay. [24] Proposed an upgraded Trust detection procedure to improve the possibility of detecting and preventing the black hole nodes. Here, the nature of the malicious nodes extended the risk of threats and seduces the operations.…”
Section: Black Holementioning
confidence: 99%
“…These attacks were Blackhole, Denial of service (DoS, and wormhole. The comparison was made for their throughput, End to End Delay, and Packet Delivery Ratio (PDR) Authors in [5] proposed a MANET trust model that uses a combination of direct, indirect, and mutual trust values among network nodes to reflect the behavior of sensor nodes. The aim was to test out the effectiveness of a secured node can be routed within the network.…”
Section: Related Work On Security Framework In Manetsmentioning
confidence: 99%